Research Opportunities for Cancer Associated with Indoor Air Pollution from Solid-Fuel Combustion - Reid, Britt C. (National Institute of Environmental Health Sciences, 2012)
Background: Indoor air pollution (IAP) derived largely from the use of solid fuels for cooking and heating affects about 3 billion people worldwide, resulting in substantial adverse health outcomes, including cancer. Women and children from developing countries are the most exposed populations. A workshop was held in Arlington, Virginia, 9–11 May 2011, to better understand women’s and children’s potential health effects from IAP in developing countries. Workshop participants included international scientists, manufacturers, policy and regulatory officials, community leaders, and advocates who held extensive discussions to help identify future research needs. Objectives: Our objective was to identify research opportunities regarding IAP and cancer, including research questions that could be incorporated into studies of interventions to reduce IAP exposure. In this commentary, we describe the state of the science in understanding IAP and its associations with cancer and suggest research opportunities for improving our understanding of the issues. Discussion: Opportunities for research on IAP and cancer include studies of the effect of IAP on cancers other than lung cancer; studies of genetic factors that modify susceptibility; studies to determine whether the effects of IAP are mediated via germline, somatic, and/or epigenetic changes; and studies of the effects of IAP exposure via dermal and/or oral routes. Conclusions: IAP from indoor coal use increases the risk of lung cancer. Installing chimneys can reduce risk, and some genotypes, including GSTM1-null, can increase risk. Additional research is needed regarding the effects of IAP on other cancers and the effects of different types of solid fuels, oral and dermal routes of IAP exposure, genetic and epigenetic mechanisms, and genetic susceptibility.